Common genetic variants associated with telomere length confer risk for neuroblastoma and other childhood cancers. (1st April 2016) - Walsh, Kyle M.; Whitehead, Todd P.; de Smith, Adam J.; Smirnov, Ivan V.; Park, Minsun; Endicott, Alyson A.; Francis, Stephen S.; Codd, Veryan; ,; Samani, Nilesh J.; Metayer, Catherine; Wiemels, Joseph L.
Summary: We identify inherited genetic variants associated with telomere length that may also confer risk for childhood cancers. Analyses reveal that genetic predisposition to longer telomere length increased risk of neuroblastoma, and potentially risk of osteosarcoma and acute lymphoblastic leukemia. Abstract: Aberrant telomere lengthening is an important feature of cancer cells in adults and children. In addition to somatic mutations, germline polymorphisms in telomere maintenance genes impact telomere length. Whether these telomere-associated polymorphisms affect risk of childhood malignancies remains largely unexplored. We collected genome-wide data from three groups with pediatric malignancies [neuroblastoma ( N = 1516), acute lymphoblastic leukemia (ALL) ( N = 958) and osteosarcoma ( N = 660)] and three control populations ( N = 6892). Using case–control comparisons, we analyzed eight single nucleotide polymorphisms (SNPs) in genes definitively associated with interindividual variation in leukocyte telomere length (LTL) in prior genome-wide association studies: ACYP2, TERC, NAF1, TERT, OBFC1, CTC1, ZNF208 and RTEL1 . Six of these SNPs were associated ( P < 0.05) with neuroblastoma risk, one with leukemia risk and one with osteosarcoma risk. The allele associated with longer LTL increased cancer risk for all these significantly associated SNPs. Using a weighted linear combination of the eight LTL-associated SNPs, we observed that neuroblastoma patients were predisposed to longer LTL than controls, with each standard deviation increase in genotypically estimated LTL associated with a 1.15-fold increased odds of neuroblastoma (95%CI = 1.09–1.22; P = 7.9×10 −7 ). This effect was more pronounced in adolescent-onset neuroblastoma patients (OR = 1.46; 95%CI = 1.03–2.08). A one standard deviation increase in genotypically estimated LTL was more weakly associated with osteosarcoma risk (OR = 1.10; 95%CI = 1.01–1.19; P = 0.017) and leukemia risk (OR = 1.07; 95%CI = 1.00–1.14; P = 0.044), specifically for leukemia patients who relapsed (OR = 1.19; 95%CI = 1.01–1.40; P = 0.043). These results indicate that genetic predisposition to longer LTL is a newly identified risk factor for neuroblastoma and potentially for other cancers of childhood.